The moderating role of social support in the relationship between alexithymia and problematic smartphone use among Chinese depressed adolescents: a cross-sectional study - Liu, Shumiao; Wu, Yufeng; Sun, Fengxia; Zhou, Yongjie; Yin, Aihua (Frontiers in Psychiatry, 2025)
BackgroundAlexithymia is closely related to problematic smartphone use (PSU) in adolescents, but its mechanism in adolescents with depression is still unclear. The aim of this study was to investigate the predictive effect of alexithymia on PSU in depressed adolescents and to examine the moderating effect of social support (family, friends, significant others) on this relationship.MethodsA total of 2343 adolescents with depressive disorder aged 12–18 years from 14 medical institutions in China were included in this cross-sectional study. The Toronto Alexithymia Scale, Mobile Phone Addiction Index and Multidimensional Perceived Social Support Scale were used to evaluate the core variables. Hierarchical regression analysis was used to test the moderating effect after controlling demographic variables.ResultsAlexithymia was significantly and positively associated with PSU (r = 0.343, p < 0.01), with Difficulty in Recognizing Feelings having the strongest association (r = 0.348). Stratified regression revealed that family support (B = -0.625, p = 0.005) and friend support (B = -0.577, p = 0.013) significantly attenuated the positive predictive effect of alexithymia on PSU, whereas there was no significant moderating effect of significant others support.ConclusionResearch shows that social support mitigates the risk of (PSU) among depressed adolescents with alexithymia, with family and friend support as key protective factors. These findings highlight the need for clinical screening and interventions targeting adolescents with alexithymia and low social support, who are at high risk for PSU. Integrating family systems therapy and friend support programs into clinical interventions may enhance emotional regulation and reduce smartphone dependence, thereby improving depressive symptoms.